Effective spiritual care of elderly patients following the kaigo method at Hue Central Hospital - Chuong, Phan Canh; Trung, Nguyen Thanh; Linh, Tran Thi Yen; Hong, Nguyen Thi; Thu, Mai Ba; Sang, Le Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Elderly care according to the Kaigo method is a specialized care system developed in Japan. It aims to provide holistic nursing support for the elderly, encompassing physical, psychological, and social needs. This research aimed to evaluate the effectiveness of the Kaigo method in the mental care of elderly patients at the Department of General Internal Medicine and Geriatrics, Hue Central Hospital. Methods: An intervention study without a control group was conducted, involving pre - and post - intervention monitoring of 114 patients over 60 years old receiving inpatient treatment. Results: The average happiness index according to WHO-5 before and after the intervention was 42.26 ± 10.45 and 84.12 ± 12.1, respectively. The average quality of life score according to the EQ 5D5L scale before and after the intervention was 17.54 ± 1.22 and 11.25 ± 3.06, respectively. The inpatient experience score before the intervention was 3.14 ± 0.73 and 3.92 ± 0.91 after the intervention. Factors related to the change in the happiness index in the intervention group included the quality of life and inpatient experience scores. Conclusion: Spiritual care for elderly patients using the Kaigo method significantly improved the happiness index and quality of life and inpatient experience.